Newton, Einstein and Barth on time and eternity - Qu, Li (Scottish journal of theology, 2014)
For two hundred years after 1687, Newton's notion of absolute time dominated the world of physics. However, Newtonian metaphysical absolute time is so ideal that it may only be realised and actualised by God. In the early twentieth century, Einstein breaks this dominant understanding of time fundamentally by his Special Theory of Relativity and General Theory of Relativity. In the Einsteinian paradigm, we are forced to think no longer of space and time but rather to look at a four-dimensional space-time continuum, in which time appears to be more space-like than temporal. The Newtonian theory implies that there is an absolute, dominant point from which the universe can be observed, whereas Einstein argues for the opposite: there can be no vantage perspective and no universal present by which God can divide past and future.Barth takes a trinitarian approach to interpret the concept of time. For Barth, the Father is coeternal with the Son and the Holy Spirit. The eternal immanent Trinity acts concretely as the temporal economic Trinity, thus the triune God is pre-, supra- and post- to us. In actual temporality, the Father, Son and Holy Spirit transcend time concretely in our history and penetrate time absolutely from divine eternity. God's eternity is both transcendent and immanent to human time.Such a trinitarian temporality might serve as a ‘dynamic privileged perspective’ since time, energy and movement are all created by God from eternity. On the one hand, the triune Creator transcends his creature and its creaturely form – time absolutely; on the other hand, even when God enters time and moves together with the time ‘uniformly’ in the Son and the Holy Spirit, he becomes concretely simultaneous with all time. Also the Barthian perspective might provide something which is lacking in Einstein's relative time, i.e. the direction of time from the past to the future. Since every historical event in Einsteinian four-dimensional continuum is posited as a static space-time slice and Einstein equations are time-reversible, there is no ontological difference between time dimensions at all. However, in Barth's trinitarian opinion, such extraordinary events as the creation, resurrection and Pentecost are ontologically superior to other events in human history because they do change our temporality in an absolute way. Penetrated by the trinitarian eternity, those discrete space-time slices also become communicable and hence take genuine temporal characteristics, i.e. the past, present and future.